Thermoelectric Thin Films Materials and Devices - Mele, Paolo; Narducci, Dario; Ohta, Michihiro; Biswas, Kaniskha; Morante, Juan; Saini, Shrikant; Endo, Tamio (Springer International Publishing : Imprint: Springer, 2019)
This book will provide readers with deep insight into the intriguing science of thermoelectric thin films. It serves as a fundamental information source on the techniques and methodologies involved in thermoelectric thin film growth, characterization and device processing. This book involves widespread contributions on several categories of thermoelectric thin films: oxides, chalcogenides, iodates, nitrides and polymers. This will serve as an invaluable resource for experts to consolidate their knowledge and will provide insight and inspiration to beginners wishing to learn about thermoelectric thin films. Provides a single-source reference on a wide spectrum of topics related to thermoelectric thin films, from organic chemistry to devices, from physical chemistry to applied physics, from synthesis to device implementation; Covers several categories of thermoelectric thin films based on different material approaches such as oxides, chalcogenides, iodates, nitrides and polymers; Discusses synthesis, characterization, and device processing of thermoelectric thin films, as well as the nanoengineering approach to tailor the properties of the used materials at the nanoscale level.